2011
DOI: 10.1016/j.cognition.2010.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism influences inhibitory control in auditory comprehension

Abstract: Bilinguals have been shown to outperform monolinguals at suppressing task-irrelevant information. The present study aimed to identify how processing linguistic ambiguity during auditory comprehension may be associated with inhibitory control. Monolinguals and bilinguals listened to words in their native language (English) and identified them among four pictures while their eye-movements were tracked. Each target picture (e.g., hamper) appeared together with a similar-sounding within-language competitor picture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
204
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(238 citation statements)
references
References 74 publications
(111 reference statements)
33
204
1
Order By: Relevance
“…Constant recruitment of this mechanism by bilinguals leads to better behavioral performance on executive function tasks that measure cognitive control for both verbal and nonverbal stimuli (Costa et al, 2008;Blumenfeld and Marian, 2011). The present study shows that this prolonged bilingual experience leads to enhanced WM connectivity, which may be one mechanism underlying the bilingual advantage observed in EF performance.…”
Section: Discussionmentioning
confidence: 99%
“…Constant recruitment of this mechanism by bilinguals leads to better behavioral performance on executive function tasks that measure cognitive control for both verbal and nonverbal stimuli (Costa et al, 2008;Blumenfeld and Marian, 2011). The present study shows that this prolonged bilingual experience leads to enhanced WM connectivity, which may be one mechanism underlying the bilingual advantage observed in EF performance.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that bilinguals may have advantage over monolinguals in tasks with linguistic stimuli (BLUMENFELD; MARIAN, 2011;FILIPPI et al, 2012). The advantage is shown in tasks in which interference must be suppressed for successful processing of the target stimulus.…”
Section: Studies With Linguistic Tasksmentioning
confidence: 99%
“…This hypothesis was formulated with relation to the studies of Blumenfeld and Marian (2011) and Filippi et al (2012), who found that bilinguals have superior to monolinguals in tasks involving linguistic interference suppression performance.…”
Section: Effects Of Bilingualism and Multilingualism On Executive Funmentioning
confidence: 99%
See 2 more Smart Citations